Basolateral Amygdala Mediates Central Mechanosensory Feedback of Musculoskeletal System - Liu, Nian; Li, Botai; Zhang, Lu; Yang, Dazhi; Yang, Fan (Frontiers in Molecular Neuroscience, 2022)
Musculoskeletal diseases, such as osteoporosis and sarcopenia, are tremendous and growing public health concerns. Considering the intimate functional relationship between muscle and bone throughout development, growth, and aging, muscle provides the primary source of skeletal loading through contraction force. However, significant gaps exist in our knowledge regarding the role of muscle in bone homeostasis and little is known regarding the mechanism through which the central nervous system responds and regulates unloading-induced bone loss. Here, we showed that the basolateral amygdala (BLA) and medial part of the central nucleus (CeM) are anatomically connected with the musculoskeletal system. Unloading-induced bone loss is accompanied by a decrease in serum Sema3A levels as well as sensory denervation. In vivo fiber photometry recordings indicated that the mechanical signal is integrated by the BLA and CeM within 24 h and subsequently regulates bone remodeling. Moreover, chemogenetic activation of BLACaMKII neurons mitigates severe bone loss caused by mechanical unloading via increased serum levels of Sema3A and sensory innervation. These results indicate that the BLA integrates the mechanosensory signals rapidly and mediates the systemic hormonal secretion of Sema3A to maintain bone homeostasis.